Epidemiology of Fractures in a Tropical Country - Pascal Chigblo; Éric Lawson; Iréti Fiacre Tidjani; Adébola Padonou; Christian Térance Nezien; Oswald Goukodadja; Soumaïla Madougou; Aristote Hans-Moevi Akue (European Scientific Journal, ESJ, 2017)
Introduction: The increasing number of vehicles and the proliferation of two-wheeled vehicles accentuate the frequency of fractures in our country. The aim of this study is to describe the epidemiology of fractures in Cotonou. Materials and Methods: This prospective two-year study focused on all patients admitted to the emergency department of the National Teaching Hospital of Cotonou for a fracture injury. Results: 1794 fractures were collected in 1432 patients. Fractures accounted for 24.9% of surgical emergencies. The average age was 33.7 years (29 days - 90 years). The dominance was male with a sex ratio of 3.62. Etiological circumstances were dominated by road traffic accidents (75.8%), The etiological circumstances were dominated by road accidents (75.8%), motorcyclists being the most affected (48.5%). The admission average was 27.33 hours (15 minutes - 29 days). Fractures preferentially sat on the lower limbs (64.4%). In descending order of frequency, were distinguished the fractures of leg (32.2%), of the femur (19.8%) and of the forearm (14.8%). Conclusion: fractures are common. The etiologies are dominated by traffic accident. The lesions predominate in the lower limb. The establishment of good road safety policy (improving track conditions, extension of the highway code ...) would reduce their frequency.